Direct observation of solidification behaviors of Fe-Mn-Si alloys during TIG spot welding using synchrotron X-ray. (15th July 2022) - Nagira, Tomoya; Nakamura, Terumi; Yoshinaka, Fumiyoshi; Sawaguchi, Takahiro; Aoki, Yasuhiro; Kamai, Masayoshi; Fujii, Hidetoshi; Takeuchi, Akihisa; Uesugi, Masayuki
Abstract: To perform a detailed investigation of the solidification behaviors of alloys during welding, it is crucial to observe the dendrite-scale microstructural evolution. Therefore, by utilizing high-spatial resolution X-ray imaging and diffraction, in this study, a successful technique was developed for the time-resolved and in situ observation of δ- and γ-Fe dendrite growth and solidification cracking behaviors of Fe-Mn-Si alloys during TIG spot welding. For the specimen solidifying in the austenite (A) mode, solidification cracking initiated at the center of the weld pool and propagated toward the weld pool boundary through high-angle dendrite boundaries. However, for the specimen solidifying in a unique ferrite-austenite (FA) mode, many equiaxed γ-Fe dendrites nucleated in front of the growing columnar δ-Fe dendrites. Solidification cracking propagation was suppressed by the numerous equiaxed γ-Fe dendrites that developed at the center of the weld pool. Therefore, the solidification mode significantly influenced the solidification cracking susceptibility. Graphical abstract: Image, graphical abstract